2019
DOI: 10.1007/s11837-019-03361-7
|View full text |Cite
|
Sign up to set email alerts
|

In Situ High-Cycle Fatigue Reveals Importance of Grain Boundary Structure in Nanocrystalline Cu-Zr

Abstract: Nanocrystalline metals typically have high fatigue strengths, but low resistance to crack propagation. Amorphous intergranular films are disordered grain boundary complexions that have been shown to delay crack nucleation and slow crack propagation during monotonic loading by diffusing grain boundary strain concentrations, suggesting they may also be beneficial for fatigue properties. To probe this hypothesis, in situ transmission electron microscopy fatigue cycling is performed on Cu-1 at.% Zr thin films ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Atomistic modeling results from Pal et al [44] suggested that AIFs can resist propagation of both parallel and perpendicular cracks by blunting the crack tip. In situ TEM fatigue experiments by Schuler et al [45] provided confirmation of such crack tip blunting by AIF-containing microstructures, as well as distribution of plastic activity into a larger region inside the material. AIFs will also dampen localization progression by inhibiting grain coarsening that leads to localized softening in the shear path, as amorphous grain boundary complexions have been observed to have a stabilizing effect on grain size [26,46].…”
Section: Resultsmentioning
confidence: 94%
“…Atomistic modeling results from Pal et al [44] suggested that AIFs can resist propagation of both parallel and perpendicular cracks by blunting the crack tip. In situ TEM fatigue experiments by Schuler et al [45] provided confirmation of such crack tip blunting by AIF-containing microstructures, as well as distribution of plastic activity into a larger region inside the material. AIFs will also dampen localization progression by inhibiting grain coarsening that leads to localized softening in the shear path, as amorphous grain boundary complexions have been observed to have a stabilizing effect on grain size [26,46].…”
Section: Resultsmentioning
confidence: 94%
“…It is widely accepted that amorphous GB phases release shear stress accumulation by promoting GB sliding, 77–79 and they are also known to promote steady fatigue crack growth and even plasticity distribution by diffusing the strain concentration at the GBs. 80,81 Conversely, no evidence of similar nanostructures could be found in the micrographs of annealed Ni–Mo–W thin films. The lack of strain-accommodating regions could be a source of expedited stress concentration at the GBs of annealed thin films, but the scarcity of clear amorphous phases in the as-deposited films blurs a definitive analysis.…”
Section: Discussionmentioning
confidence: 95%
“…This change in the deformation mechanism provides superior mechanical properties to NC materials [19]. Due to these nano-scale features, the NC materials have enhanced strength [20][21][22], improved fatigue life [23][24][25], superior wear resistance [26,27], improved hardness [20,28,29], higher specific heat [30,31], and improved coefficient of thermal expansion [32][33][34]. However, researchers also revealed that NC materials have lower ductility [35].…”
Section: Processing Of Nc Materialsmentioning
confidence: 99%